2007
DOI: 10.5216/rpt.v23i2.20026
|View full text |Cite
|
Sign up to set email alerts
|

ATIVIDADE ANTI-EMBRIOGENICA "ÍN VITRO" DO ALBENDAZOL SOBRE OVOS DE Lagochilascaris minor Leiper,1909

Abstract: Avaliou-se a ação do Albendazol sobre cultura de ovos de Lagochilascaris minor. Aproximadamente ISxlO3 ovos recém-eliminados em fezes de gatos infectados experimentalmente com L. minor foram colocados em placas de Petri com 400 mg de Albendazol e deixados à temperatura ambiente por 45 dias. O mesmo procedimento foi feito com ovos embrionados. Os ovos dos grupos controle de ambos os experimentos foram deixados em solução de formol a 1% em temperatura ambiente. Após o período de 45 dias, todos os ovos foram exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Therefore, more studies are needed on the anthelmintic activity in the different stages of the parasite. For example, albendazole has been tested in vitro in suspension at a dose of 400 mg/10 ml of 1% formalin solution on newly eliminated eggs and embryonated eggs 37 . These authors found that, at this dosage, the drug prevents egg embryogenesis but has no effect on embryonated eggs, so its activity is restricted to embryogenesis, and there is no effect on larvae 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, more studies are needed on the anthelmintic activity in the different stages of the parasite. For example, albendazole has been tested in vitro in suspension at a dose of 400 mg/10 ml of 1% formalin solution on newly eliminated eggs and embryonated eggs 37 . These authors found that, at this dosage, the drug prevents egg embryogenesis but has no effect on embryonated eggs, so its activity is restricted to embryogenesis, and there is no effect on larvae 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the drugs tested experimentally, only albendazole prevents egg embryogenesis 37 . Ivermectin used at a higher than recommended dosage and levamisole hydrochloride have no activity against encysted larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Vieira et ai. (14), usando o albendazol na mesma dosagem (400mg/kg), por 30 dias consecutivos, sobre ovos embrionados e ovos não embrionados (in vitró), verificaram que a droga impedia a embriogênese dos ovos.…”
unclassified